Tribunals (Scotland) Act 2014 : consultation on draft regulations regarding, (1) the transfer of functions and members of the additional support needs tribunals for Scotland to the Scottish tribunals, (2) the rules of procedure for the first-tier tribunal for Scotland Health and Education Chamber, (3) the composition of the first-tier and upper tribunals for Scotland, and, (4) the eligibility for ordinary membership of the first-tier tribunal for Scotland Health and Education Chamber.: consultation on draft regulations regarding, (1) the transfer of functions and members of the additional support needs tribunals for Scotland to the Scottish tribunals, (2) the rules of procedure for the first-tier tribunal for Scotland Health and Education Chamber, (3) the composition of the first-tier and upper tribunals for Scotland, and, (4) the eligibility for ordinary membership of the first-tier tribunal for Scotland Health and Education Chamber. (2017) - Unknown
No abstract available